PERANCANGAN SISTEM INFORMASI AKADEMIK MENGGUNAKAN METODE PIECES PADA MTS DARUSSA’ADAH JAKARTA - Rusma Insan Nurachim (Jurnal Teknologi Informatika dan Komputer, 2018)
The development of education in Indonesia, experienced a lot of increase. One of them is the use of computers and internet as a means of supporting teaching and learning activities. Some schools have used internet facilities to access course materials, grades and other academic data. As a support for making an application, it needs an integrated system in it. System is a network of procedures in the form of a sequence of activities that are interconnected, gathered together to achieve certain goals. In evaluating the existing system used PIECES method (Performance, Information, Economics, Control, Efficiency and Service) .MTS Darussa'Adah Jakarta is a school that developed since 1990s. The location is quite strategic and qualified teaching staff make MTS Darussa'Adah Jakarta as the choice of some parents for the education of their children. However, the minimal promotional media and data processing is still manual, had caused some obstacles. For that, need to be designed a website that is not only as a medium of advertising, but also as a supporter of academic data processing. The results of this application is displayed data value of students and other data reports.